In Vitro Characterization of the Neurapheresis™ System for the Treatment of Cryptococcal Meningitis. (4th October 2017) - Charalambous, Lefko; Ballard, Christi; Ejikeme, Tiffany; Ashraf, Bilal; Pagadala, Promila; Giamberardino, Charles; Hedstrom, Blake; Verbick, Laura Zitella; Mccabe, Aaron; Lad, Shivanand P; Perfect, John R
Abstract: Background: Cryptococcal Meningitis (CM) is the most common cause of fungal meningitis in adults. Treatment for CM is an induction, consolidation, and maintenance approach with antifungal agents. but is associated with continued high morbidity and mortality. Here we describe the in vitro characterization of a catheter-based extracorporeal filtration system (Neurapheresis™) as an alternative mechanical intervention for the filtration of C. neoformans cells, polysaccharide antigen, and inflammatory mediators from infected cerebrospinal fluid (CSF). Methods: H99, a clinical strain of C. neoformans, was grown overnight in YPD before being transferred to diluted Saboraud/MOPS media for 24 hours to induce cell proliferation and capsule growth, respectively. Cells were diluted to clinically relevant concentrations (1 × 10 7 and 1 × 10 5 cells/mL) in 150 mL of Saboraud/MOPS and passed through the closed-loop system with either 100 or 5 kDa tangential flow filters. Samples were taken every full CSF volume filtration cycle (150 mL) for quantification of yeast load, antigen, and cytokines. Infected human CSF was used to obtain cytokine data. Results: Both tangential flow filter sizes thoroughly cleared yeasts. Over 24 cycles, we consistently observed a 5-log drop (≥99%) in colony forming units (CFUs), which resulted in complete elimination at a starting concentration of 1 × 10 5 cells/mL. Both 100 and 5kDa achieved a substantial antigen reduction (using CrAg LFA [initial titer]-[final titer]; [1:10 5 ]–[1:10 4 ] and [1:10 5 ]–[1:10 2 ], respectively). A similar reduction in cytokine levels (IL-1ra, IL-6, TNF, CRP, and CXCL10) in infected human CSF was also achieved (100 kDa reduced all cytokines except IL-1ra by >95% baseline, and 5kDa removed >95% of all quantified cytokines). Conclusion: Continuous filtration via Neurapheresis is capable of eliminating CSF CFU burden in an in vitro CM model. Future iterations may include adjunctive infusions with drug therapies to further accelerate eradication of yeasts. Significant reduction of cryptococcal antigen and inflammatory cytokines also has potential for controlling the neuro-inflammatory storm that accompanies CM. Disclosures: B. Hedstrom, Minnetronix, Inc.: Employee, Salary; L. Zitella Verbick, Minnetronix, Inc.: Employee, Salary; A. Mccabe, Minnetronix, Inc.: Employee, Salary; S. P. Lad, Minnetronix, Inc.: Collaborator and Scientific Advisor, Licensing agreement or royalty, Research grant and Research support